Chemical constituents of Walsura pinnata hassk / Mahfuzah Yusoff - Yusoff, Mahfuzah (2012)
The chromatographic separation of the n-hexane extract from the stem bark of Walsura pinnata Hassk (Meliaceae) which was collected at Kuala Lipis, Pahang, led to the isolation of nine chemical constituents. Their structures were characterized to be ledol (115), oplopanone (116), betulonic acid (117), oleanonic acid (118), 3-oxoolean-11-en- 13β(28)-olide (119), 12α-hydroxy-3-oxooleanano-28,13-lactone (120), 3-oxoursolic acid (121), 3-ketours-11-en-13β(28)-olide (122), 3β-hydroxy-5-glutinen-28-oic acid (123). The structural elucidation of these compounds was determined by spectroscopic data interpretation. Betulonic acid (117) and 3β-hydroxy-5-glutinen-28-oic acid (123) were found to be cytotoxic against a series of human cancer cell lines with an IC50 = 19 μM, 18 μM on HepG2; 12 μM, 25 μM on MCF-7 and 13 μM, 21 μM on HSC-2 respectively.